Digestibility and Metabolic Utilization and Nutritional Value of Leucaena leucocephala (Lam.) Leaves Meal Incorporated in the Diets of Indigenous Senegal Chickens - Ayssiwede, S.B.; Dieng, A.; Chrysostome, C.; Ossebi, W.; Hornick, J.L.; Missohou, A. (International Journal of Poultry Science, 2010)
In the prospect of the Leuceana leucocephala leaves meal using as a protein ingredient source for indigenous Senegal chickens diets, a study was carried out to determine their nutrient utilization and nutritional value when incorporated at various levels in the diets. Twenty adult indigenous chickens with an average body weight of 1.22 kg were conducted in metabolic cages and allocated in four groups of five birds each. The groups were corresponded to four dietary treatments (LL0, LL7, LL14 and LL21) containing respectively 0, 7, 14 and 21% of Leuceana leaves meal. During the trial, birds were weighed at the beginning and at the end. Feed offered and refused, collected fresh excreta were weighed daily and the droppings were oven-dried at 60oC and ground per bird for six days. The ingredients and experimental diets used and collected excreta were subjected to chemical analyses. Results showed that the Leuceana leaves were relatively rich in protein (24.9% DM), ether extract (6.4% DM), crude fiber (14.2% DM) and Neutral detergent fiber (22.4% DM). It contained respectively 43.1% and 11.4% DM of nitrogen free extract and ash, particularly calcium (1.8%) and potassium (1.1% DM) and 2573.8 kcal/kg DM of metabolizable energy. The results of the trial showed that the inclusion of L. leucocephala leaves meal in the diet at 21% level, has no significant adverse effect on feed intake, average daily weight gain, feed conversion ratio and nutrients utilization (except ether extract) of adult indigenous Senegal chickens. It has significantly (p